Evaluación de la calidad microbiológica en quesos frescos de producción artesanal expendidos en el mercado cerrado Latacunga. - Moreano Terán, Nancy Fabiola. (2021)
Fresh cheese is a food widely consumed by the Ecuadorian population; however, the consumer is unaware of the microbiological quality of the product, representing a health risk. The general objective of the research work is the microbiological evaluation of the fresh cheeses sold in the Latacunga closed market, which was carried out using microbiological techniques and under the specifications of the Technical Standard INEN 1528: 2012, which determines the microbiological quality of the product. through permissible parameters of good quality levels and acceptable quality levels. The results obtained report that 75% of the samples analyzed exceed the microbiological load in E. Coli, in the Enterobacteria analysis the count exceeds the permissible parameters, obtaining values between 10⁴ to 10⁵ cfu/g, 50% of the samples report presence of Listeria Monocytogenes, due to the exposure of the product in commercial activities there are conditions for the development of Salmonella and Staphylococcus aureus. Therefore, it is determined that the fresh cheeses sold in the Latacunga closed market have poor hygienic conditions, affecting the quality of the product.